Coding of communication calls in the subcortical and cortical structures of the auditory system - Suta, D; Popelár, J; Syka, J (Physiological research, 2008)
The processing of species-specific communication signals in the auditory system represents an important aspect of animal behavior and is crucial for its social interactions, reproduction, and survival. In this article the neuronal mechanisms underlying the processing of communication signals in the higher centers of the auditory system--inferior colliculus (IC), medial geniculate body (MGB) and auditory cortex (AC)--are reviewed, with particular attention to the guinea pig. The selectivity of neuronal responses for individual calls in these auditory centers in the guinea pig is usually low--most neurons respond to calls as well as to artificial sounds; the coding of complex sounds in the central auditory nuclei is apparently based on the representation of temporal and spectral features of acoustical stimuli in neural networks. Neuronal response patterns in the IC reliably match the sound envelope for calls characterized by one or more short impulses, but do not exactly fit the envelope for long calls. Also, the main spectral peaks are represented by neuronal firing rates in the IC. In comparison to the IC, response patterns in the MGB and AC demonstrate a less precise representation of the sound envelope, especially in the case of longer calls. The spectral representation is worse in the case of low-frequency calls, but not in the case of broad-band calls. The emotional content of the call may influence neuronal responses in the auditory pathway, which can be demonstrated by stimulation with time-reversed calls or by measurements performed under different levels of anesthesia. The investigation of the principles of the neural coding of species-specific vocalizations offers some keys for understanding the neural mechanisms underlying human speech perception.
Keywords: akustická stimulace; Animals; Geniculate Bodies; Emotions; Inferior Colliculi; Songbirds; Acoustic Stimulation; Chiroptera; Action Potentials; sluchové korové centrum; emoce; zpěvní ptáci; neurony; anestezie; Auditory Perception; morčata; Primates; sluchová percepce; Cats; Neurons; Vocalization, Animal; metathalamus; Anesthesia; Guinea Pigs; Auditory Cortex; zvířata; primáti; vokalizace zvířat; kočky; colliculus inferior; akční potenciály